The Effect of Total Asset Turnover, Debt to Equity Ratio, Return on Equity, and Sales Growth on Price to Book Value : (An Empirical Study on Property and Real Estate Subsector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period) (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the impact of Total Asset Turnover, Debt to Equity Ratio, Return on Equity, and Sales Growth on the Price to Book Value of the Property and Real Estate sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. This research is a quantitative study using purposive sampling to determine the sample, resulting in 50 companies out of 84. The analytical model employed is multiple linear regression. The results of this study indicate that Total Asset Turnover, Debt to Equity Ratio, and Sales Growth have a significant positive effect on Price to Book Value, while Return on Equity has no effect on Price to Book Value.